IMPLEMENTATION OF CORPORATE INNOVATION IN INDONESIAN STATE-OWNED ENTERPRISES - Prawidhana, Arno (Jurnal Bina Bangsa Ekonomika, 2025)
State-owned enterprises (SOEs) in Indonesia constantly need to adapt to change and adjustments in their respective industries. Corporate innovation may offer a systematic guidance for companies to navigate these challenges and give them a positive impact in the long run. Through qualitative research, the study identifies key factors influencing the success of corporate innovation in SOEs. The study finds the importance of aligning innovation initiatives with the vision and strategy of the organization, as well as establishing a proper innovation ecosystem, including necessary steps and supporting elements. When properly implemented, innovation can help companies address both short-term goals, such as financial gains and operational efficiency, and long-term aspirations, including fostering an innovation culture and achieving sustainable growth in dynamic market environments.